Study on the Intercultural Communication of Traditional Chinese Culture - Yang, Hongjuan; Tang, Jun (Pacific International Journal, 2023)
In the era of globalization and the rapid growth of we-media, intercultural communication plays a crucial role in promoting traditional Chinese culture on an international scale. China has been actively engaged in advancing intercultural communication as a means to enhance its cultural soft power, fostering the high-quality development of its culture and contributing to the realization of the Chinese nation’s rejuvenation. This study focuses on the intercultural communication of traditional Chinese culture, using Li Ziqi’s vlogs as a case study, in order to provide updated insights for the promotion of China’s traditional culture in diverse cultural contexts, effectively conveying a long-standing image of Chinese civilization. Through the analysis of themes and categorization of Li Ziqi’s short videos, the study defines the cultural symbolism conveyed through these videos, explains the factors that contribute to their success, and draws conclusions that can enlighten the international dissemination of traditional Chinese culture. Furthermore, it serves as a model case for practicing intercultural communication of traditional Chinese culture. The study’s findings emphasize the importance for Chinese cultural promotion to seize the opportunities presented by we-media development, accurately targeting the needs of overseas audiences to enhance the effectiveness of cultural communication, and facilitating a deeper understanding of the rich connotations of traditional Chinese culture among foreign audiences